IMPLEMENTASI SISTEM MANAJEMEN INFORMASI BAZNAS (SiMBA) DALAM MENGOPTIMALKAN PENGELOLAAN ZAKAT DI KABUPATEN HULU SUNGAI SELATAN - Siti Raudatun Ni'mah; Norwilistini (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
This study aims on the presence of SiMBA at BAZNAS South Hulu Sungai Regency, and the implementation of SiMBA in zakat management can make zakat management more effective, efficient, and improve the benefits of zakat to realize community welfare and poverty alleviation. The aim is to determine the implementation of SiMBA in optimizing zakat management at BAZNAS South Hulu Sungai Regency. The results of the study revealed that the implementation of SiMBA at BAZNAS South Hulu Sungai Regency has been able to optimize zakat management from the stages of collection, distribution, operations, and reporting, showing significant improvements due to supporting factors such as adequate internet network, data transmission capability, and supporting applications such as muzakki corner. it is also possible that there are inhibiting factors in SiMBA management, such as skilled human resources, internet network disruptions, and incomplete data provided by muzakki or mustahik, which prevents data input into the SiMBA application.